2020
DOI: 10.3390/microorganisms8071068
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Edwardsiella piscicida CK108 Transcriptome Profiles with Subinhibitory Concentrations of Phenol and Formalin Reveal New Insights into Bacterial Pathogenesis Mechanisms

Abstract: Phenol and formalin are major water pollutants that are frequently discharged into the aquatic milieu. These chemicals can affect broad domains of life, including microorganisms. Aquatic pollutants, unlike terrestrial pollutants, are easily diluted in water environments and exist at a sub-inhibitory concentration (sub-IC), thus not directly inhibiting bacterial growth. However, they can modulate gene expression profiles. The sub-IC values of phenol and formalin were measured by minimal inhibitory concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 67 publications
(83 reference statements)
0
19
0
Order By: Relevance
“…In recent years, researches on the pathogenic mechanism of E. piscicida have become a research hotspot in the field of aquatic animal diseases. A variety of pathogenic factors and systems, such as adhesion factors, iron uptake regulators, antiserum ability, type III and VI secretion systems, hemolysin, catalase, cytotoxin, TAM, two-component system, density induction systems, flagellin, lysozyme inhibitors, intracellular survival mechanisms, and some environmental stress factors have been discovered and studied ( Yin et al, 2018 ; Leung et al, 2019 ; He et al, 2020 ; Li et al, 2020 ; Yoon et al, 2020 ). However, toxin-antitoxin (TA) system, an important stress and antibiotic resistance factor/system, are totally unknown in E. piscicida .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researches on the pathogenic mechanism of E. piscicida have become a research hotspot in the field of aquatic animal diseases. A variety of pathogenic factors and systems, such as adhesion factors, iron uptake regulators, antiserum ability, type III and VI secretion systems, hemolysin, catalase, cytotoxin, TAM, two-component system, density induction systems, flagellin, lysozyme inhibitors, intracellular survival mechanisms, and some environmental stress factors have been discovered and studied ( Yin et al, 2018 ; Leung et al, 2019 ; He et al, 2020 ; Li et al, 2020 ; Yoon et al, 2020 ). However, toxin-antitoxin (TA) system, an important stress and antibiotic resistance factor/system, are totally unknown in E. piscicida .…”
Section: Introductionmentioning
confidence: 99%
“…Although a microorganism possesses genes for stress response, a specific gene may not be actively expressed as RNA unless cells are exposed to severe growth conditions. RNA sequencing (RNA-seq) is a useful technology to investigate the stress response mechanisms in various microorganisms [ 9 , 10 , 11 , 12 ]. For example, transcriptome analysis of Staphylococcus aureus revealed the increased cell adhesion and biofilm formation in response to low concentrations of ampicillin [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…piscicida were revealed. In addition to canonical virulence systems T3SS, T6SS, adhesion factors, haemolysin, catalase, antiserum related factor and regulator factors such as Fur and Hfq (Hu et al, 2014; Leung et al, 2019; Tan et al, 2019; Yin et al, 2018; Yoon et al, 2020; Zhang et al, 2018, 2019), some novel virulence genes and resistance genes were also identified in E . piscicida .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many virulence-related factors/systems in E. piscicida were revealed. In addition to canonical virulence systems T3SS, T6SS, adhesion factors, haemolysin, catalase, antiserum related factor and regulator factors such as Fur and Hfq (Hu et al, 2014;Leung et al, 2019;Tan et al, 2019;Yin et al, 2018;Yoon et al, 2020;Zhang et al, 2018Zhang et al, , 2019, some novel virulence genes and resistance genes were also identified in E. piscicida. For example, it was reported that Glu6P transport regulatory protein UhpA played a role in regulating the virulence gene expression (Ye et al, 2021).…”
Section: Introductionmentioning
confidence: 99%